Інклюзивне освітнє середовище в закладах вищої освіти: шляхи створення - Грень, Лариса Миколаївна; Черкашин, Андрій Іванович; Чеботарьов, Микола Корнійович (Національний технічний університет "Харківський політехнічний інститут", 2021)
У статті розкрито суть таких понять, як: “інклюзивне навчання”, “інклюзивне освітнє середовище”, “інклюзивно-ресурсний центр”, “особа з особливими освітніми потребами”; наведено основні етапи розвитку та становлення інклюзивної освіти у світовій практиці; розглянуто правову основу інклюзивного навчання в Україні та умови, за яких заклад вищої освіти набуває статусу інклюзивного; визначено суттєві зміни у нормативно-правовому забезпеченні щодо покращення інклюзивного освітнього середовища у закладах вищої освіти; сконцентровано увагу на тому, що необхідною умовою для створення інклюзивного середовища закладу вищої освіти потребує теоретична і методологічна база інклюзивної освіти, підвищення рівня підготовки викладацько-професорського складу до роботи з особами з особовими освітніми потребами, матеріально-технічна та програмно-методична забезпеченість.

In the article, the essence of such notions as “inclusive education”, “inclusive education environment”, “inclusive resource center”, “a person with special education needs” is disclosed; the main stages in inclusive education development and formation in the word practices are given; the legal framework for inclusive education in Ukraine is considered as well as conditions in terms of which a higher education institution obtains the inclusive status; considerable changes in the regulative-legal framework concerning inclusive education environment improvement at higher education institutions (HEI) in recent period are determined; focused on that a necessary precondition for efficient forming of inclusive environment at a HEI is improvement of theoretical and methodological foundation of inclusive education, raising the training level of the teaching personnel who are to work with persons with special education needs, their material, technical, digital, and methodological support.
Inclusive educational environment at higher education institutions: ways of creation
Keywords: особа з особливими освітніми потребами; нормативно-правове забезпечення; a person with special education needs; regulative and legal support